Sistema de auditoria interna de la cooperativa de producción y comercialización La Clementina - Erika Mercedes Díaz Gómez, Erika Mercedes (2020)
In summary, the COOPROCLEM internal audit system presents the following problems regarding the audit program applied to date: Lack of control in the distribution of production inputs.- This problem is attributed to poor coverage planning by the winemakers in the information provided in the daily tour by the auditor Problems with the workforce, delays and delivery of products always go hand in hand and are related to the lack of supplies since when there is a shortage of any material they are forced to paralyze their work, which generates inconveniences since the Staff, having no work materials, do not carry out their activities, generating losses of time and money by not completing production quotas. The lack of control in the provision of fuels is a problem directly related to the audit planning since they are in charge of verifying and estimating the daily consumption of the machines, which then have to stop their work due to the lack of either diesel in the case of irrigation and drainage pumps and other motors or gasoline in the case of auxiliary pumps and equipment complementary to production. Finally, the loss and diversion of supplies in the winery and in the field is a responsibility that, according to the production manager, not only falls on the auditors, but on all the administrative personnel, mainly, since the control of supplies depends on them once delivered in their respective areas.